Creation of the first Hartford Consensus compliant elementary school in the USA. Issue 1 (26th September 2016) - Ramly, Elie; Bohnen, Jordan D; Fagenholz, Peter; Yeh, Dante; Velmahos, George; DeMoya, Marc; Kaafarani, Haytham; Butler, Katheryn; Lee, Jarone; King, David R
Abstract : Background: The Hartford Consensus established a framework for minimizing deaths due to mass shootings, specifically eliminating preventable deaths due to limb exsanguination. Two major principles defined within this framework are (1) redefining the first responder role and (2) the ubiquitous availability of proper training in application of hemorrhage control techniques, including tourniquets. We hypothesized that this hemorrhage control posture could be fully translated into an elementary school. Methods: Following institutional review board approval, all teachers at a prekindergarten through 8th grade elementary school underwent short, intensive instruction on their role as a first responder, as well as indications and proper technique for hemorrhage control and tourniquet application for limb exsanguination. All teachers self-reported their confidence in their role as a first responder as well as tourniquet application indications and technique before and after instruction. Following instruction, teachers were evaluated on proper tourniquet application technique on a simulated limb to assess competence. Results: 26 elementary school teachers and 2 administrative staff underwent training. All reported low confidence in their role as a first responder and in tourniquet application indication and technique before training. Following training, all teachers reported high confidence. Testing demonstrated all teachers were competent in the tourniquet application technique. Following training, each classroom was equipped with a purpose-made commercial tourniquet, and a dedicated hemorrhage control bag was placed in the school's central administrative office. Conclusions: All teachers were successfully trained to act as first responders and in correct hemorrhage control techniques, which was verified by testing. This is the first elementary school to universally adopt a hemorrhage control posture to eliminate preventable deaths from limb exsanguination advocated by the Hartford Consensus.